A Study of Fungal Growth in Alternative Media of Breadfruit (Artocarpus altilis) in Direct and Powder Formulations: Studi pertumbuhan jamur pada media alternatif sukun (Artocarpus altilis) pada sediaan langsung dan powder - Erpi Nurdin Nurdin (Biocelebes, 2021)
Background: Medium is a material consisting of a mixture of nutrients which functions as a place to grow microbes. Semi-synthetic media such as PDAs contain sufficient carbohydrates so that they are good for use for fungal growth. This medium is quite a lot needed in the breeding of Candida albicans and Aspergillus niger both in the laboratory. However, the price of this media is quite expensive and limited, while the need is increasing so that alternative media are needed to replace the breeding. Objective: To determine the growth rate of unicellular and multicellular fungi on breadfruit alternative media (Artocarpus altilis) in semi-solid and powder dosage forms. Methods: This study is a descriptive study with a laboratory instrumental approach Results: An alternative medium of tribal composition, dextrose, so that the semi-solid dosage form and powder form could grow Candida albicans and Aspergillus niger well.